2018
DOI: 10.1111/bjso.12240
|View full text |Cite
|
Sign up to set email alerts
|

Positive stereotypes, negative outcomes: Reminders of the positive components of complementary gender stereotypes impair performance in counter‐stereotypical tasks

Abstract: Gender stereotypes are complementary: Women are perceived to be communal but not agentic, whereas men are perceived to be agentic but not communal. The present research tested whether exposure to reminders of the positive components of these gender stereotypes can lead to stereotype threat and subsequent performance deficits on the complementary dimension. Study 1 (N = 116 female participants) revealed that compared to a control/no-stereotype condition, exposure to reminders of the stereotype about women's com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 79 publications
4
35
1
1
Order By: Relevance
“…Therefore, the results have shown that women have higher mean scores in emotional coping style than men and that men have higher mean scores in rational and detachment coping styles than women, this difference could be due to the internalization of gender stereotypes that associate men with reason and women with emotion. Despite the fact that such stereotypes portray women and men as opposites and complementary [ 60 ], with the exception of detachment coping style, the significant predictors of psychological distress were practically identical for women and men, suggesting that they both react in a very similar way in terms of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results have shown that women have higher mean scores in emotional coping style than men and that men have higher mean scores in rational and detachment coping styles than women, this difference could be due to the internalization of gender stereotypes that associate men with reason and women with emotion. Despite the fact that such stereotypes portray women and men as opposites and complementary [ 60 ], with the exception of detachment coping style, the significant predictors of psychological distress were practically identical for women and men, suggesting that they both react in a very similar way in terms of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences are congruent with gender stereotypes and traditional socialization patterns. In this sense, agency is central to men, who are characterized by focusing on the self and orient towards independence and the achievement of personal goals; communion is central to women, more oriented to other people and toward forming connections [54].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the changes that have taken place in Western societies, which highlight women’s access to higher education and participation in the workforce, gender stereotypes still persist [12]. Gender stereotypes characterize men and women as complementary: women are perceived to be communal but not agentic whereas men are perceived to be agentic but not communal [13]. Such stereotypes do not only describe typical differences between women and men, as they also prescribe what and how they should behave, to the point of influencing on the way women and men define themselves and are treated by others [14].…”
Section: Introductionmentioning
confidence: 99%